Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja Rumah Sakit dengan Pendekatan ILO OSHMS 2001 - Dewi, Hafizah Rani Putri Andam; Wahyudi, Rizqi; Gusvita, Rinda (Teknoin, 2025)
The application of Occupational Safety and Health (K3), especially in the field of service facilities, is needed to reduce the occurrence of work accidents in the human resources involved. One way to prevent work accidents is to implement hazard risk control, namely the Occupational Health and Safety Management System (SMK3). This study aims to find out the results of SMK3 implementation, find out how far the implementation level of SMK3 is by involving the ILO OSHMS 2001 guidelines, and provide recommendations for improvement according to the results obtained. This research involved 40 respondents who answered 30 statement items and were divided into 5 elements of ILO OSHMS 2001 namely Policy Assessment, Organizing, Planning and Implementation, Evaluation and Corrective Actions. The results showed that the average SMK3 achievement level for all elements was 86% and was included in the level category between good and very good. Based on these results, recommendations for improvement are given according to SMK3 actions with the help of a risk control hierarchy so that the discussion is more focused and recommendations for improvements can be implemented properly.